Shopping for Change : Consumer Activism and the Possibilities of Purchasing Power - Hyman, Louis; Tohill, Joseph (Ithaca, NY : Cornell University Press, 2017)
Consuming with a conscience is one of the fastest growing forms of political participation worldwide. Every day we make decisions about how to spend our money and, for the socially conscious, these decisions matter. Political consumers "buy green" for the environment or they "buy pink" to combat breast cancer. They boycott Taco Bell to support migrant workers or Burger King to save the rainforest.But can we overcome the limitations of consumer identity, the conservative pull of consumer choice, co-optation by corporate marketers, and other pitfalls of consumer activism in order to marshal the possibilities of consumer power? Can we, quite literally, shop for change? Shopping for Change brings together the historical and contemporary perspectives of academics and activists to show readers what has been possible for consumer activists in the past and what might be possible for today's consumer activists.ContributorsKyle Asquith, University of Windsor; Dawson Barrett, Del Mar College; Lawrence Black, University of York; Madeline Brambilla, Northeastern University; Joshua Carreiro, Springfield Technical Community College, Springfield, MA; H. Louise Davis, Miami University; Jeffrey Demsky, San Bernardino Valley College; Tracey Deutsch, University of Minnesota-Twin Cities; Mara Einstein, Queens College, CUNY; Bart Elmore, University of Alabama; Sarah Elvins, University of Manitoba; Daniel Faber, Northeastern University; Julie Guard, University of Manitoba; Louis Hyman, ILR School, Cornell University; Meredith Katz, Virginia Commonwealth University; Randall Kaufman, Miami Dade College-Homestead Campus; Larry Kirsh, IMR Health Economics, Portland, OR; Katrina Lacher, University of Central Oklahoma; Bettina Liverant, University of Calgary; Amy Lubitow, Portland State University; Robert N. Mayer, University of Utah; Michelle McDonald, Stockton University; Wendy Wiedenhoft Murphy, John Carroll University; Mark W. Robbins, Del Mar College;Jessica Stewart, Cornell University;Joseph Tohill, York University and Ryerson University; Allison Ward, Queen's University and McMaster University; Philip Wight, Brandeis University
Frontmatter -- CONTENTS -- Acknowledgements -- Introduction / Hyman, Louis / Tohill, Joseph -- 1. Consuming with a Conscience / McDonald, Michelle Craig -- 2. Boycotts, Buycotts, and Legislation / Murphy, Wendy Wiedenhoft -- 3. Making a Market for Consumers / Liverant, Bettina -- 4. Making a Middle-Class "Public" / Robbins, Mark -- 5. You Are Purchasing Prosperity! / Ward, Allison -- 6. Making Money in Hard Times / Elvins, Sarah -- 7. Protecting the "Guinea Pig Children" / Asquith, Kyle -- 8. Our Economic Way Out / Carreiro, Joshua L. -- 9. Not Buying It / Demsky, Jeffrey Scott / Kaufman, Randall -- 10. Canada's Citizen Housewives / Guard, Julie -- 11. "The Consumer Goes to War" Consumer Politics in the United States and Canada during the Second World War / Tohill, Joseph -- 12. From the Great Society to Giant / Black, Lawrence -- 13. The Countercultural Roots of Green Consumerism / Wight, Philip A. -- 14. Purchasing Change / Davis, H. Louise -- 15. Buying a Better World / Einstein, Mara -- 16. What about the Cause? / Faber, Daniel / Lubitow, Amy / Brambilla, Madeline -- 17. The Making of a Coke CAN / Elmore, Bartow -- 18. Boot the Bell / Barrett, Dawson -- 19. Where's the Beef . . . From? / Lacher, Katrina -- 20. The Sweatshop Effect / Katz, Meredith -- 21. Hating Wal-Mart, Loving Target, and the Contradictions of Supply Chain Capitalism / Stewart, Jessica -- 22. Ports are the New Factories / Hyman, Louis -- 23. To Speak in One Voice / Mayer, Robert N. / Kirsch, Larry -- 24. On Demand -- CONTRIBUTORS -- NOTES -- INDEX
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: Consumer movements -- North America; Consumption (Economics) -- Political aspects -- North America; Social action -- North America; Business (General).; U.S. History; POLITICAL SCIENCE / Political Process / Political Advocacy